2014
DOI: 10.1108/ijqrm-04-2013-0064
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of quality management system based on ISO9001:2008 and its effects on customer satisfaction case study

Abstract: Purpose – The purpose of this paper is to discuss the effect of the ISO 9001 quality management system on customer satisfaction and show an application of an analytic hierarchy process (AHP)-based method for measuring the customer satisfaction index (CSI). This will be useful to anyone who wants to have an ISO 9001 quality management system in his or her organization. Design/methodology/approach – This paper describes an ISO 9001 quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
(26 reference statements)
0
14
0
1
Order By: Relevance
“…Government's efforts in fulfilling the desire for speed and accuracy will have a positive impact on satisfaction with public services [Bashir et al, 2012]. SMM has an influence on the production process, purchase and after purchase, research findings prove that there is a positive correlation with the purchase of standardized kitchen worktops and make buyers feel satisfied with the services provided [Nabavi et al, 2014]. Satisfaction is a person's feelings regarding comfort or disappointment resulting from comparisons between perceived product performance (outcomes) in relation to their expectations [Kotler, 2007].…”
Section: Review Of Literaturesmentioning
confidence: 99%
“…Government's efforts in fulfilling the desire for speed and accuracy will have a positive impact on satisfaction with public services [Bashir et al, 2012]. SMM has an influence on the production process, purchase and after purchase, research findings prove that there is a positive correlation with the purchase of standardized kitchen worktops and make buyers feel satisfied with the services provided [Nabavi et al, 2014]. Satisfaction is a person's feelings regarding comfort or disappointment resulting from comparisons between perceived product performance (outcomes) in relation to their expectations [Kotler, 2007].…”
Section: Review Of Literaturesmentioning
confidence: 99%
“…A Danish study found that ISO certified companies had a significantly higher rate of return than before they were certified (Haversjo, 2000). QA systems have also been associated with an increase in customer satisfaction (Nabavi et al, 2014).…”
Section: Creativity and Innovationmentioning
confidence: 99%
“…Although the literature points out that quality management and environmental management are closely linked to the risk management of an organization (Arenhart et al, 2013;Nabavi et al, 2014;Srinivasu et al, 2010), it is surprising that by 2015 the standards NBR ISO 9001 (Quality Management Systems -QMS) e ISO 14001 (Environmental Management Systems -EMS) did not have mandatory requirements for linking quality management to risk management actions. Based on this shortcoming, this study examines how the new revisions to the standards published in the second half of 2015 incorporate risk-minded requirements to reorient organizations into their business operations, how they perceive and integrate those requirements with company intelligence.…”
Section: Introdutionmentioning
confidence: 99%